1981
DOI: 10.3758/bf03202013
|View full text |Cite
|
Sign up to set email alerts
|

The perceptual properties of electrocutaneous stimulation: Sensory quality, subjective intensity, and intensity-duration relation

Abstract: A preliminary and two main experiments designed to examine the perceptual properties of electrocutaneous stimulation are reported. The stimuli used were single short pulses varying in intensity and duration. In Experiment 1, the exponents of power functions fitted to electrocutaneous magnitude estimation data were determined together with the sensory qualities induced by electrical stimulation. The results showed that there was no correlation between the exponent values and the sensory qualities. The mean expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 38 publications
3
31
0
Order By: Relevance
“…Therefore, they vary largely over the literature [82,84], from buzzing to sharp pain. Variations in perceived sensations with electrotactile stimuli are related to stimulus intensity, electrode characteristics, preparation of the skin, and the use of cathodic or anodic stimulation [81,[85][86]. It was shown that sensations perceived by amputees do not differ from the sensations of nondisabled subjects for percutaneous stimulation [87].…”
Section: Feedback Requirement 3: Interpretability and Intuitivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they vary largely over the literature [82,84], from buzzing to sharp pain. Variations in perceived sensations with electrotactile stimuli are related to stimulus intensity, electrode characteristics, preparation of the skin, and the use of cathodic or anodic stimulation [81,[85][86]. It was shown that sensations perceived by amputees do not differ from the sensations of nondisabled subjects for percutaneous stimulation [87].…”
Section: Feedback Requirement 3: Interpretability and Intuitivenessmentioning
confidence: 99%
“…For electrotactile stimulation, this is mainly due to the relationship between stimulus duration and stimulus intensity [80][81], and for vibrotactile stimulation, this depends on the position of stimulation [82]. The perceived stimulus intensity is influenced by the intensity, the duration and number of bursts of stimulation, the housing of the stimulator, the characteristics of the preceding stimulus, and the number of simultaneous stimuli [83].…”
Section: Feedback Requirement 3: Interpretability and Intuitivenessmentioning
confidence: 99%
“…The apparatus was the same as that used in Tashiro and Higashiyama (1981). A constant-current stimulator was used: a dc power supply (Kikusui Electronics Model PAF), operated at 400 V, was connected to resistors ranging from .5 to 67 MQ, accurate to within 1010.…”
Section: Apparatusmentioning
confidence: 99%
“…Previous studies on electrical stimulation have reported diverse slopes of the power functions fitted to magnitude estimates: Bujas, Szabo, Kovacic, and Rohacek (1975) S. S. Stevens (1960), and S. S. Stevens, Carton, and Shickman (1958) obtained high slopes of 3.5 or more; Babkoff (1976Babkoff ( , 1978 and Tashiro and Higashiyama (1981) obtained low slopes of.9 to 1.2; Cross, Tursky, and Lodge (1975), Rollman and Harris (1987), and Sachs, Miller, and Grant (1980) obtained moderate slopes of 1.7 to 2.5. Moreover, Rollman and Harris (1987) noted considerable individual differences in the slope of the power function for electrical shock.…”
Section: Discussionmentioning
confidence: 99%